40 Correlation of relationship between infliximab and adalimumab trough and antibody levels with clinical response rates at completion of induction therapy. (5th April 2017) - Tighe, D; Smith, S; O'Connor, A; Breslin, N; Ryan, B; McNamara, D
Abstract : Background: Anti-TNFa therapies have improved response rates in inflammatory bowel disease. However primary loss of response is problematic. Aim: Aim of this study was to explore relationship between infliximab (IFX) and adalimumab (ADA) trough and antibody levels with clinical response. Method: This was a prospective, single centre study. Patients were recruited from July 2015-August 2016. Inclusion criteria were patients older than 17 years with IBD who started treatment with anti-TNFa drugs (infliximab/adalimumab) Patient demographics, clinical history were collected from electronic records. Clinical disease activity indexes were performed (Harvey-Bradshaw Index for Crohn's disease (CD), and partial Mayo scores for Ulcerative colitis (UC)). Clinical response defined as reduction in HBI≤3 or reduction in partial Mayo score ≤4 and <30% from baseline. Anti-TNFa trough and antibody levels were measured using ELISA. Results: 35 patients were recruited; 23 CD, 12 UC. 18 patients treated with ADA, 17 IFX. Mean age 40.3 years, 62.9% female, 34.3% thiopurines, 25.7% prior anti-TNFa exposure. Response rate 51.4%, 33.3% for ADA, 70.6% for IFX. Overall trough levels were 12.5 ug/ml for IFX, 4.4 ug/ml for ADA. There was clear link between higher anti-TNFa trough levels at induction with clinical response. For infliximab, mean trough levels in responders were 16.4 ug/ml (IQR 8.4-22.7) versus 5.3 ug/ml(IQR 0.5–8.8) for non-responders (p value 0.02 95% CI: 1.5 to 20.7). Similarly there was a link between higher ADA levels with clinical response, though not statistically significant. Responders mean trough 6.6 ug/ml versus non-responders 3.0 ug/ml (p value 0.14). Antibody formation occurred in 28.5%. Conclusions: Higher anti-TNFa trough levels at induction are associated with improved clinical response.